Code-Mixing and Code-Switching in Teaching Listening Skills to Intermediate 3 Students at LBPP LIA Bekasi (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
This study discusses the form and function of code-switching and code-mixing used by the teacher in teaching listening skills to the Intermediate 3 students at LBPP-LIA Bekasi. The phenomenon of implementing code-switching and codemixing codes does not only occur in multilingual societies but also in the foreign language learning process in the classroom where teacher and students use two different languages. The strategy of using code-switching and code-mixing is expected to facilitate foreign language students particularly in learning how to listen where the teacher and students engage in interaction using the language that students are learning. Qualitative method is used to analyze data. From the results of data analysis, it was revealed that the teacher often switches codes when teaching listening skills for both code- switching from English to Bahasa and vice versa. The teacher also mixes the code in the form of morphemes, words, phrases, and clauses. The aim of the teacher to change and mix codes in teaching can be seen from the functions of using code-switching and code-mixing. The confirmation function, for example, is used by the teacher so that students do not misunderstand the topic learned. Other functions also have different objectives to facilitate students learning how to listen in English interactively in the classroom.